Forecasts of petroleum demand - Kugelevičius, Jonas A.; Kuprys, Algirdas; Kugelevičius, Jonas (Transport, 2007)
Trends of consumption of petroleum products in Lithuania are analyzed. It is shown that these trends during the transition period to the market economy are not stable. Therefore, methods and models of the comparative analysis are proposed for the statistical modelling trends of consumption of petroleum products, comparing the relative indicators of consumption of petroleum products in transition economy and in the European Community of 15 EU developed market countries. Long‐term forecasts of consumption of petroleum products in Lithuania for the perspective of 2010–2025 were calculated on the basis of perspective scenarios of statistical models. Forecasts of final consumption of petroleum products as well as automotive fuel demands are presented. First Published Online: 27 Oct 2010